CHEMICAL COMPOSITION AND ACARICIDAL ACTIVITIES OF JATROPHA CURCAS L. EXTRACT AGAINST ORIENTAL RED MITE, EUTETRANYCHUS ORIENTALIS (KLEIN) (ACARI: TETRANYCHIDAE) - H. Alahyane; R. Ait Babahmad; H. Aboussaid; Y. Atibi; A. Aimrane; K. Oufdou; S. El Messoussi (Journal of Animal and Plant Sciences, 2020)
Laboratory bioassays were conducted to evaluate the acaricidal activities of the ethanolic extract of Jatropha curcas L. leaves (Family: Euphorbiaceae) against adult females of oriental red mite, Eutetranychus orientalis. The leaf dip technique and direct application were adopted to assess the toxicity, fertility, repellency and ovicidal effects of different doses (0.1–10 mg/mL) of the ethanolic extracts of J. curcas L. leaves. We found that this extract increased mortality and reduced fecundity in a dose-dependent manner. Leaf discs treated with increasing doses (0.05, 0.5, 1 and 5 mg/mL) of the extract also showed a high percentage of repellency (94.12%) while treated eggs with these increasing doses showed a remarkable increase in the eggs’ mortality 7 days after treatment, i.e., 72.00% at 5 mg/mL. We confirmed the presence of secondary metabolites and showed an abundance of phenolic compounds, flavonoids, flavonols and tannins with different concentrations.
Keywords: Jatropha curcas L. extract; Eutetranychus orientalis; repellency; ovicidal effect; secondary metabolites